Enabling change in EFL teachers' ideologies about grammar and grammar teaching through alternative pedagogies. (February 2018) - Robertson, Margaret; Macdonald, Shem; Starks, Donna; Nicholas, Howard
Abstract: For pedagogies to change, teachers undertaking professional development need to engage in deep reflective thinking about what they bring with them, what their professional programs offer and what their teaching contexts expect. In this paper, we describe a set of activities used to encourage EFL in-service teachers to engage with multiple examples of pedagogies related to one grammatical item and to reflect on how these activities mediate and change their beliefs about grammar and grammar teaching. Informed by a view of pedagogy that combines teaching with culturally-situated purposes, theories and beliefs, we analyse changes in the ways these in-service teachers conceptualize grammar; develop a deeper understanding of pedagogical approaches to grammar and show a willingness to engage with alternative approaches; and alter their ideologies around their EFL praxis as a way to make informed decisions about their pedagogies and take more control over their teaching.